Port Planning Under Deep Uncertainty - Gelfi, Mustarakh; Achiari, Hendra (UI Scholars Hub, 2020)
This study is about the port planning under deep uncertainty using the framework of Scenario Based-Adaptive Port Planning (SB-APP). The framework gives sequential workflow on designing the future masterplan of the port. The alternative layouts and adaptive actions are some important outcomes of the framework. The port has to realize that uncertainties persevere and are very likely to influence the decision making for future planning. Instead of ignoring uncertainties, the port needs to make contingency planning to deal with them. This study has benefits to make a robust terminal masterplan of the port.